An analysis about the English curricular strategy for Physical Culture degree - Liliana Margarita Martinez Hernandez; Marta Arroyo Carmona; Fidelina Castillo Morales; Alida Nersa Paneque Ginarte (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2018)
This research is aimed at stating an analysis of the English Curricular Strategy tendencies and regularities in the Physical Culture degree of Pinar del Rio University, leading to introduce actions able to reduce insufficiencies in the already mentioned strategy implementation. To meet the goal, it was used mainly empirical methods such as documents 'analysis, the survey and the interview. It was considered a sample of 56 students from I, II, III and IV years (Daytime Regular Course) of Physical Culture Faculty and 10 teachers who teach the different subjects in these years. As the result a group of insufficiencies transcends, which convey that in the practice, the strategy has not achieved the mission it was designed for. The work suggests some aspects that should be taken into consideration to optimize the strategy application in the context of the new policy about the English teaching improvement in the Cuban Higher Education